2022
DOI: 10.1038/s41598-022-18841-1
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule mediated inhibition of protein cargo recognition by peroxisomal transport receptor PEX5 is toxic to Trypanosoma

Abstract: Trypanosomiases are life-threatening infections of humans and livestock, and novel effective therapeutic approaches are needed. Trypanosoma compartmentalize glycolysis into specialized organelles termed glycosomes. Most of the trypanosomal glycolytic enzymes harbor a peroxisomal targeting signal-1 (PTS1) which is recognized by the soluble receptor PEX5 to facilitate docking and translocation of the cargo into the glycosomal lumen. Given its pivotal role in the glycosomal protein import, the PEX5–PTS1 interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…In this study, fluorescence polarization-based high-throughput screening (FP-HTS) was employed to identify inhibitors of the LdPEX5-PTS1 interaction. Prior to this study, investigations focusing on LdPEX5-PTS1 interaction had not been reported, with only one study on TcPEX5-PTS1 interaction, which identified 48 hits from HTS of a ~30,000 compound library resulting in a 0.16% hit rate [28]. The hit rate from this study was even lower (0.054%) possibly due to the differences in substrate concentrations, Kd values, or the structural features of compounds in the library.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In this study, fluorescence polarization-based high-throughput screening (FP-HTS) was employed to identify inhibitors of the LdPEX5-PTS1 interaction. Prior to this study, investigations focusing on LdPEX5-PTS1 interaction had not been reported, with only one study on TcPEX5-PTS1 interaction, which identified 48 hits from HTS of a ~30,000 compound library resulting in a 0.16% hit rate [28]. The hit rate from this study was even lower (0.054%) possibly due to the differences in substrate concentrations, Kd values, or the structural features of compounds in the library.…”
Section: Discussionmentioning
confidence: 86%
“…Recently, the PEX14-PEX5 protein-protein interaction, essential for glycosomal protein import, has been highlighted as an attractive target for Trypanosoma inhibitor discovery [25,26]. Furthermore, hit compounds that inhibit the interaction between TcPEX5 and PTS1 cargo have been shown to effectively kill T. brucei parasites in cell culture [28]. Notably, despite belonging to the same kinetoplastid parasites group as Trypanosoma, no research has yet explored this interaction in Leishmania parasites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, targeting glycosomal biogenesis has become an attractive drug target. This druggability of the glycosome biogenesis machinery has been genetically validated using RNA interference mediated knockdown of various peroxins ( Moyersoen et al., 2003 ; Barros-Alvarez et al., 2014 ; Banerjee et al., 2019 ), as well as pharmacologically through identification and development of small molecule inhibitors that block peroxin protein-protein interactions (PPIs) ( Dawidowski et al., 2017 ; Kalel et al., 2018 ; Banerjee et al., 2021 ; Napolitano et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, targeting glycosomal biogenesis has become an attractive drug target (Kalel et al, 2018). This has been genetically validated using RNA interference mediated knockdown of various peroxins (Moyersoen et al, 2003;Barros-Alvarez et al, 2014;Banerjee et al, 2019), as well as pharmacologically through identification and development of small molecule inhibitors that block peroxin protein-protein interactions (PPIs) (Dawidowski et al, 2017;Banerjee et al, 2021;Napolitano et al, 2022).…”
Section: Introductionmentioning
confidence: 99%